(untitled) (Actas Médicas (Ecuador), 2021)
Introduction: According to epidemiological surveillance studies in the United States and the SEER database, a behavior has been observed in which the incidence of colorectal cancer is increasing in people under 50 years of age while it is decreasing in older patients.In men and women under 50 years of age, the increase is constant at a rate of 2.1% per year from 1992 to 2012. And it has also been seen that in young individuals the disease is more advanced at the time of diagnosis and the Tumors are less well differentiated than in older adults.General objective: To determine the characteristics of colorectal cancer and its surgical treatment in patients under 50 years of age.Methodological design: Observational, retrospective, cross-sectional, descriptive study type.Results: Since 2010, at the Teodoro Maldonado Carbo Hospital (TMC), 12 cases (7%) were observed until in 2016 the number tripled to 37 (21%): of which 101 were men (57 %), while in the female sex 76 (43%). CRC in young adults occurred more frequently between the ages of 41 and 50, where 101 (57%) were seen, and in patients between the ages of 31 and 40 there were only 63 (36%); the mean age was 41.26 years with a range of 17 to 50 years. standard deviation of 7.0; Minimum age of 19 and maximum age of 50 years.Symptomatic patients 172 (97%).Conclusions: An increase in the presentation of CRC patients under 50 years of age is observed since 2010, where only 12 (7%) were observed, until 2016, where, in 6 years, the number of cases tripled to 37 (21 %).The average age of presentation is 41.2; it is more common in men than in women; Cancer in most cases is of sporadic, symptomatic origin. Histology is usually adenocarcinoma.